1994
DOI: 10.1002/stem.5530120409
|View full text |Cite
|
Sign up to set email alerts
|

Production of human granulocyte colony stimulating factor by various kinds of stromal cells in vitro detected by enzyme immunoassay and in situ hybridization

Abstract: Abstract. Production of human granulocyte colony stimulating factor (G-CSF) by stromal cells was studied in vitro. Induction of G-CSF by interleukin 1 (IL-1) and lipopolysaccharide (LPS) was compared using enzyme immunoassay in various kinds of stromal cells. Primary human bone marrow stromal cells, a human bone marrow-derived stromal cell line (KM-102), and peripheral blood monocytes secreted small amounts of G-CSF without stimulation, while vascular endothelid cells and skin fibroblasts secreted G-CSF only w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…As seen in Figure 2E, over 80% of Kasumi-1 cells exhibited cell surface expression of the G-CSF receptor compared to <20% of SKNO-1 and HMC1.1 cells. In agreement, it has been previously shown that Kasumi-1 cells express significantly more G-CSF receptor mRNA than SKNO-1 cells 11 . These data suggest that the cell surface expression of the G-CSF receptor is correlated with the capacity of the cytokine to reverse sensitivity to c-KIT inhibition in Kasumi-1 cells and its failure to do so in SKNO-1 and HMC1.1 cells.…”
supporting
confidence: 89%
“…As seen in Figure 2E, over 80% of Kasumi-1 cells exhibited cell surface expression of the G-CSF receptor compared to <20% of SKNO-1 and HMC1.1 cells. In agreement, it has been previously shown that Kasumi-1 cells express significantly more G-CSF receptor mRNA than SKNO-1 cells 11 . These data suggest that the cell surface expression of the G-CSF receptor is correlated with the capacity of the cytokine to reverse sensitivity to c-KIT inhibition in Kasumi-1 cells and its failure to do so in SKNO-1 and HMC1.1 cells.…”
supporting
confidence: 89%
“…It has also been reported that inflammation-related products, such as IL-1 and lipopolysaccharide, stimulate G-CSF production by fibroblasts originating from the skin [27]. In this study, we showed that G-CSF levels in wounded tissue reached a plateau as early as 3 hours after total skin excision, and spindle-to ovalshaped mesenchymal cells (probably fibroblasts) in the wounded tissue express G-CSF.…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, we hypothesized that macrophages directly regulate G-CSF expression. We used OP9 bone-marrow stromal cells, which have been known to secrete G-CSF especially after stimulation by either lipopolysaccharide or IL-1 [33], [34], [35]. To study whether macrophages regulate G-CSF expression through secreted cytokines, we treated OP9 cells with conditioned media from either bone-marrow or peritoneal derived macrophages of wild type mice.…”
Section: Resultsmentioning
confidence: 99%